Relationship between innovation‐led HR policy, strategy, and firm performance: A serial mediation investigation. Issue 5 (9th March 2018) - Do, Hoa; Budhwar, Pawan S.; Patel, Charmi
Abstract : This research examines the relationship between innovation‐led strategy and innovation‐led HR policy (hereafter, management initiatives) and innovation performance. Our research model is theorized and tested in the Vietnamese context, based on the servant leadership theory and componential theory of creativity. We draw upon constructs of management initiatives, servant leadership, employee creativity, and firm innovation to hypothesize serial mediation mechanisms linking management initiatives to firm performance. Using a multilevel sample of 56 service firms, we conduct multilevel path analyses. We find that (a) individual‐level servant leadership mediates the top‐down relationship between management initiatives and employee creativity, (b) employee creativity mediates the bottom‐up relationship between individual‐level servant leadership and firm‐level innovation, and (c) firm‐level innovation mediates the bottom‐up relationship between employee creativity and firm‐level market performance. We conclude by discussing both theoretical and practical implications.